Clinical Aspects of the Combined Course of Pulmonary Tuberculosis and Type 2 Diabetes Mellitus - Batirova Barchinoy Tadjimukhammedovna (Genius Journals, 2023)
The results of a comparative analysis of 80 cases of patients with chronic obstructive pulmonary disease (COPD) are considered: 40 cases with comorbid pathology (COPD and type 2 diabetes mellitus (DM)) and 40 cases of COPD without type 2 diabetes. The data of questionnaires, tests, clinical laboratory and instrumental indicators were analyzed. The negative role of type 2 diabetes on the course of COPD was demonstrated by such indicators as the frequency of exacerbation of COPD per year, the frequency of calls to ambulance teams, the frequency of hospitalizations due to exacerbation or worsening of the course of COPD, clinical symptoms of COPD, spirometry parameters, and indicators of cytokine and adipocytokine profiles.
Keywords: chronic obstructive pulmonary disease; cytokines; adipocytokines